Faktor-Faktor Yang Berhubungan dengan Penggunaan Alat KB di Wilayah Kerja Puskesmas Naibonat Tahun 2021 - Sunia Tungga; Yoseph Kenjam; Rina Waty Sirait (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Family planning is an effort that regulates the number of pregnancies, can use hormonal contraception. Hormonal contraceptives injections in Indonesia are increasingly used because of their effective work, practical use, relatively cheap and safe prices. However, the injection contraception has side effects, namely menstrual disorders and slow fertility in the use of tri -month injection birth control for a long time. Several factors related to the contraception, This includes education, work, knowledge, and support of the husband. The purpose of this study was to determine the factors related to the use of injecting  contraceptives the Naibonat  Health Center in 2021. This study was analytic with cross-sectional design using primary data, namely questionnaires and secondary data from the KB register record for the January-December 2020. Simple random sampling as many as 58 people Data analysis using the Chi-Square statistical test with  an error rate of 10%. The results showed a significant relationship with the use of injectable birth control is education (p-value = 0.001 <0.05), knowledge (p-value = 0.024 <0.05) and husband's support (p-value = 0,000< 05). While work has no relationship with the use of injection family planning(pvalue=0.692>0.05). The Naibonat Health Center can increase health promotion and health motivation through IEC (communication, information, and education) regarding family planning and contraceptives. To increase public knowledge about family planning and contraceptives self so that they can open community outlook and eliminate negative issues that develop in the community and suggest using long-term contraceptive methods (MKJP) such as implants, IUD, and more effective sterilization.